Estudo citogenético comparativo em espécies de maracujá (Passiflora spp.) com potencial econômico - Santos, Kedma Raíssa Gomes dos (2025)
Species of Passiflora have great economic and social importance in Brazil, being widely used in the food, ornamental, and medicinal industries. Despite this, cytogenetic studies on passionfruit are still limited, with published information available for less than 30% of the species, most of which are restricted to chromosome counting. This study aimed to analyze the karyotype of nine economically promising Passiflora species: P. alata, P. cincinnata, P. edmundoi, P. edulis, P. foetida, P. laurifolia, P. ligularis, P. luetzelburgii, and P. setacea, using double staining with the fluorochromes CMA/DAPI and fluorescent in situ hybridization (FISH). Actively growing roots were treated with 8-hydroxyquinoline, fixed in Carnoy’s solution, and subjected to double staining with CMA/DAPI and FISH. The metaphase chromosomes were photographed using an epifluorescence microscope. Eight of the analyzed species presented 2n = 18 chromosomes (x=9), while P. foetida showed 2n = 20 chromosomes (x=10). Double staining revealed distinct patterns of CMA+ blocks, indicating CG-rich heterochromatic regions. FISH revealed 4 to 6 sites of 35S rDNA located in the subterminal regions of chromosomes in the species with 2n = 18, and 6 sites of 35S rDNA located in the proximal region of the chromosomes in P. foetida. In most species, 2 sites of 5S rDNA were observed in the subterminal region of other chromosome pairs, except for P. foetida, which showed 4 sites of 5S rDNA. The observed variations in chromosomal patterns and heterochromatin distribution contribute to the understanding of the genomic diversity and cytogenetic characteristics of the genus.